Echocardiographic estimation of left ventricular filling pressures in heart transplant recipients - Zohreh Rahbar; Anahita Tavoosi; Alireza Bakhshandeh; Maryam Mehrpooya; Akram Sardari; Farnoosh Larti; Roya Sattarzadeh Badkoubeh (The Egyptian Heart Journal, 2024)
Abstract Background Echocardiographic estimation of left ventricular filling pressure in heart transplant (HTx) recipients is challenging. The ability of echocardiography to detect elevated left ventricular end-diastolic pressure (LVEDP) in HTx patients was assessed in this study. Results This descriptive cross-sectional study included 39 HTx recipients who were candidates for endomyocardial biopsy as a part of their routine post-transplantation surveillance. Doppler transthoracic echocardiography was done before the procedure, and left heart catheterization was done during the endomyocardial biopsy. Thirty-nine patients (15 female, 24 male), with a mean age of 39.6 years (range 13–70), were enrolled. A strong relation was observed between lateral E/e′ and LVEDP (R = 0.64, P value < 0.001) and average E/e′ and LVEDP (R = 0.6, P value < 0.001). The best cutoff value for LVEDP prediction was the average E/e′ ≥ 6.8 with a sensitivity of 96.15% and specificity of 68.5% for the prediction of LVEDP more than or equal to 20 mmHg. Two predictive models comprising age, gender, and lateral E/e′ or average E/e′ were also proposed. A significant relationship was also found between LVEDP and left ventricular global longitudinal strain (R = − 0.31, P value < 0.01). Conclusions Lateral E/e′ was the best predictor of LVEDP. The cutoff of average E/e′ had the best validity for the estimation of LVEDP. Despite the strong observed association, echocardiographic parameters cannot be considered a surrogate for invasive LVEDP measurements when seeking information about left ventricle filling pressure on heart transplant recipients.